Mechanical Structure Design of the Aircraft ASD Control Isolation Control - Qiongyan Shi; Jianghua Zhang (Journal of Applied Mathematics)
Aircraft control system is of key importance for flight attitude control of aircrafts. Its normal function directly determines whether the aircraft flies safely, flight delay, and dispatch reliability. Therefore, this paper designs the mechanical structure of the aircraft ASD control isolation control. Firstly, the mechanical control principle of the driving rod system is analyzed, and the isolation mechanism of pitch and roll control is designed; secondly, the control lines are classified, the transmission characteristic requirements of the aircraft control isolation system are given, the transmission ratio distribution and calculation of the aircraft control isolation system are given, and finally, the mechanism design of the aircraft ASD control isolation system is realized.